2006
DOI: 10.1063/1.2362591
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of debris from laser-produced plasma for extreme ultraviolet light source measured by laser imaging technique

Abstract: The behavior of debris generated from a laser-produced plasma (LPP) for the extreme ultraviolet light source at 13.5nm has been studied using a laser induced fluorescence (LIF) imaging system. Tin (Sn) LPPs were produced by irradiating a flat Sn plate and Sn thin films perpendicularly with a Nd:YAG laser beam. When a thin Sn film was used as a target material, the depletion of the Sn atoms was clearly observed along the Nd:YAG laser beam. The LIF system was also used for visualizing the sputtering process of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The LPP emits debris in the form of energetic ions, atoms, and molten droplets, which are difficult to control. 9,[19][20][21][22] This ablated target material vapor-deposits itself on various components within a direct line-of-sight of the plasma, including the surface of the MLM, which causes degradation in mirror reflectivity. Additional reflectivity losses are a result of ioninduced sputtering damage to the mirror itself.…”
Section: Introductionmentioning
confidence: 99%
“…The LPP emits debris in the form of energetic ions, atoms, and molten droplets, which are difficult to control. 9,[19][20][21][22] This ablated target material vapor-deposits itself on various components within a direct line-of-sight of the plasma, including the surface of the MLM, which causes degradation in mirror reflectivity. Additional reflectivity losses are a result of ioninduced sputtering damage to the mirror itself.…”
Section: Introductionmentioning
confidence: 99%
“…Although several methods have been developed for the debris mitigation, including a magnetic field trap of ions [7], foil trap [8], and so on [9], it is difficult to mitigate the neutral particle debris because they can not be controlled by electromagnetic field. In the previous study, it was found that the neutral atoms are originated from the low-intensity part of the laser spot and the deep layer from the target surface [10] and large size debris must be also generated from the same parts. So, the fundamental and general approach for debris mitigation is the use of a minimum amount of Sn that can provide a sufficient EUV power.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the dependence of CEs on the shapes and thicknesses The number of Sn atoms contained inside the dot diameter (500 µm) and the 10 nm of thickness is 7.3 × 10 13 , and radiant energy of in-band light is 10.5 mJ, which corresponds to 7.1 × 10 14 photons. Therefore each Sn atom emits 9.8 photons/atom of in-band light.…”
Section: Minimum Mass Of Sn Fuel For Sufficient Euv Radiant Energymentioning
confidence: 99%
“…2, minimum-mass Sn fuel for sufficient EUV radiation is discussed in Sec. 3 [10][11][12], reduction of neutral debris emanation is demonstrated [12,13] in Sec. 4, suppression of OOB radiation is demonstrated [14,15] Sec.…”
Section: Introductionmentioning
confidence: 99%